Implementasi Aqsamul Qur’an Dalam Memahami Ayat Tentang Etos Kerja Sumber Daya Manusia Yang Islami - Deny Az Nasta Ramadhana; Muhammad Risandi Lampah; Bunga Citra Mustika Wardhani; Boki Nurasiah; Geugeut Kinasih Wahyuni; Nura Habiba; Nandang Ihwanudin (ISLAMICA, 2022)
Ulumul Qur'an studies Aqsamul Qur'an as one of the branches of science. Aqsamul Qur'an itself is a science that studies or studies the oaths contained in the Qur'an that Allah uses to strengthen or confirm the information in it. Al-Qur'an is the last revelation that Allah sent down to the last Prophet Muhammad SAW as guidance for all humankind. It contains prohibitions and commands to worship and contains all aspects of human life, one of which is about work affairs. Islam provides clear guidelines; the motivation for worship is the main driving force in work and wants to get an award (reward). In the Qur'an itself, Allah has explained a lot that as Muslims, we must work hard and try our best to actualize ourselves as servants of Allah, which produces the best and most practical work, not only for himself but also for the benefit of others. As Muslims, they must have ethics to achieve success both in this world and in the hereafter. In several verses of the Qur'an, Allah often mentions sentences that contain qasam to emphasize something that is an essential indication in Islamic Human Resources (SDI) management, which can affect the attitudes, behaviour, performance, and work ethic of a human being.